PENGARUH BERBAGAI TAKARAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CAISIN VARIETAS SHINTA - Suparman Suparman (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
The objective of this experiment was to study the effect nitrogen fertilizer dose on growth and yield of Caisin plant (Brassica junceae L.) var. Shinta. An experiment was carried out at Experimental Station of Agriculture Faculty of Winaya Mukti University at Tanjungsari-Sumedang, with the altitude about 850 m above sea level, from February 2015 up to March 2015. Experimental design used was a Randomized Block Design (RBD), consisted of five treatment and each five replication. Dose of nitrogen (N) fertilizer tested namely : A = 0 kg ha-1 N, B = 10 kg ha-1 N, C = 20 kg ha-1 N, D = 30 kg ha-1 N, dan E = 40 kg ha-1 N. The result of this experiment showed that dose of nitrogen fertilizer be different influential on plant height at 28 Days After Planting (DAP) and 35 DAP, number of leaf at 35 DAP, weight of total dry matter per plant and weight of fresh per plant. Dose of nitrogen fertilizer 20 kg ha-1- 30 kg ha-1 give better effect on plant height at 28 Days After Planting (DAP) and 35 DAP, number of leaf at 35 DAP, weight of total dry matter per plant, and weight of fresh per plant. The optimum nitrogen fertilizer rate as much as 24.59 kg ha-1 give a weight per plant caisin maximum of 76.04 g